kin reaction to bed bugs bite reflecting erythema multiforme. Case report - Michał Andres; Andrzej Jaworek; Tomasz Stramek; Anna Wojas-Pelc (Our Dermatology Online, 2015)
Bed bugs (Cimex spp.) are wingless, hematophagous arthropods causing bites, which generates wide range of skin reaction and may be misdiagnosed with more serious disease as dermatitis herpetiformis, bullous pemphigoid or erythema multiforme. Differential diagnosis could be a challenge especially in western countries where bed bugs were forgotten since the Second World War. There are only a few reports of serious anaphylaxis after bed bugs exposition and the evidences about the role of bed bugs as vectors to some infectious diseases are not conclusive, but bites could be a source of physical ailments and psychological distress. We present a case of 24 year old female patient who had been bitten by bed bugs and primarily diagnosed with erythema multiforme. After releasing from hospitalization because of successful treatment patient developed another eruption of skin lesions, this time more characteristic to bed bugs bites during one day. The new diagnosis of bed bugs bites was confirmed with proving the presence of these arthropods in her rented apartment.